Ultra Sonic Sensor Based Blind Spot Accident Prevention System - Mahapatra, R.P.; Kumar, K.V.; Khurana, G.; Mahajan, R. (2008 International Conference on Advanced Computer Theory and Engineering, 2008)
A blind spot detection device for protection against misshapenness such as automobiles collisions, obstacles, and accident that leads to great loss of human lives and can have disastrous results.Technology used for this purpose worked by detecting the other automobiles, obstacles and bystanders. Upon detecting, the device triggers a timer that delays the activation of alarm circuitry for a brief period of time.This time delay is instituted to minimize the triggers of nuisance alarm by a momentary intrusion in the hazard zone. If the obstaclepsilas presence is still detected after the delay time, LED's and audible alarms are triggered to alert the system operator of the dangerous situation. The alarms remain activated for a time period, allowing the operator to clear the hazard zone.